CREEP ANALYSIS OF BOILER TUBES BY FEM - Taye, Chanyalew; Bazezew, Alem (Zede Journal of Ethiopian Engineers and Architects, 2023)
In this paper an andlyslY i.r developed for fhe determination of creep deformation o[ an axisymmetric boiler Illbu SlIbjeCled (0 axiJymmetnc loods. The stresseJ and Ihl’ permanent sCrams 01 a particular time and o.t the steady state cond’lion, resultmgfrom loading of the tube under constant inlernal pressure and elevlI/ed temperatUre are evaluated laking Into account the secondary creep charac/erislics of a gIven matenol. Finae element solution 1.1 pruented and discussed/or 1I class of problems Ifl which no prior analytical solution may exiSI. The method of lohman developed is an extension of Ihe direct Jfiffneu me/hod. The body IS replaced by a .!’yJtem of dllcrete triangular cross-section ring elements interconnected along circurl1Jerential nodal eircles. TIle equations of equilibrium Jar the element are derl"ved from the ’princIple oj mimmum potential. energy. The creep behaVior, of the body is formulated m terms of creep laws in current lue. Starting wah the elaslic so/ulion oj the problem, creep strains are treated as initial strains to de termme the new strell d’stribld/(Jf’lS at the end of the pre-set time interval. The procedure is repeated until the final time is reached and/or until the stress distribl4lion reaches a steady stated condition. Numerical results obtained for a tube maten’al J 2CrMoV are presented at the end.